Pemuliharaan Geowarisan di Langkawi Geopark, Malaysia - Mohd Shafeea Leman (Universiti Kebangsaan Malaysia, 2010)
Rock outcrops of Langkawi Islands are among the best known in Malaysia, exhibiting various types of sedimentary rocks throughout Palaeozoic Era and granitic rocks of Late Triassic age. On 1st June 2007 Langkawi Geopark was declared as the 52nd member of Global Geoparks Network (GGN) assisted by UNESCO. The declaration was based on the presence of several geoheritage sites and geological landscapes of national and regional significance. Among them are the oldest rock unit and oldest fossils, most complete Palaeozoic geological history and rocks, best evidences linking Langkawi islands with Gondwanaland, and most beautiful tropical island karst in Southeast Asian region. Under the National Forestry Act 1984, geoheritage resources in Langkawi Geopark are conserved as protected geosites, geological monuments, geoforest parks, and protected forest reserves. Among important geological monuments are Pulau Ular Abrasion Platform, Pulau Singa Kechil Transitional Formation Boundary, and Pulau Anak Tikus Fossil Bed, while geoforest parks comprise Machinchang Cambrian, Kilim Karst, and Dayang Bunting Marble Geoforest Parks. The Machinchang Cambrian Geoforest Park portrays landscape of Cambrian sandstone with oldest rock unit and fossils in the region. The Kilim Karst Geoforest Park exhibits outstanding tropical island karst made of richly fossiliferous limestone of Setul Formation, while the Dayang Bunting Marble Geoforest Park showcased another beautiful island karst landscape made mostly of marble of the Chuping Formation. Geoheritage conservation in Langkawi Geopark is under the jurisdiction of Forestry Department of Peninsular Malaysia, supported by researchers in handling issues related to carrying capacity of certain geosites and concerted efforts by multiple stakeholders in handling issues pertaining to environmental protection.